2019
DOI: 10.1159/000504346
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Male-Pattern Alopecia with Platelet-Rich Plasma

Abstract: <b><i>Background:</i></b> Androgenetic alopecia (AGA) affects up to 80% of men and 50% of women throughout their lifetime, causing significant discomfort. Minoxidil, finasteride, and low-level laser light therapy are the only Food and Drug Administration-approved treatments for AGA, and they have shown positive results in randomized controlled trials and meta-analyses. However, their efficacy is limited, and new therapies are needed. Injection of platelet-rich plasma (PRP), a minimally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…There were two studies in male populations not included in our meta-analyses due to insufficient data. Both studies found that PRP did not significantly affect hair growth parameters 29,30 (Table 2).…”
Section: Meta-analysis Of Hair Diameter In Womenmentioning
confidence: 94%
See 2 more Smart Citations
“…There were two studies in male populations not included in our meta-analyses due to insufficient data. Both studies found that PRP did not significantly affect hair growth parameters 29,30 (Table 2).…”
Section: Meta-analysis Of Hair Diameter In Womenmentioning
confidence: 94%
“…Whether PRP is effective for treating AGA in women is less clear, with some studies reporting a beneficial effect, 18‐25 while others report that PRP is not as effective or not effective at all for women 26‐28 . Furthermore, some studies have also reported that PRP is not effective for AGA in men 29‐32 . Thus, the effectiveness of PRP for AGA in both genders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al [29] reported recently (March 2019) the most important (for the journal's impact factor, actually J Am Acad Dermatol 7,01 IF) double-blind controlled study, including platelet number and growth factor level analysis of the effect of PRP in AGA.…”
Section: Brief History Analysis Of Prp Use In Androgenetic Alopeciamentioning
confidence: 99%
“…Regarding the number of sessions performed, different protocols have been proposed. Rodrigues et al [29] reported four subcutaneous injections of PRP. Hausauer et al [30] described, in a prospective randomized single-blinded trial conducted on 40 moderate AGA patients, two different protocols based on sub-dermal PRP injections: Protocol 1, in which three monthly sessions with a booster 3 months later were performed or protocol 2 in which sessions every 3 months were done.…”
Section: Growth Factorsmentioning
confidence: 99%